Psychological aspects of the work with students at a technical university; 1st Russian Seminar on Engineering Education under the theme: 1st Siberian Seminar on Engineering Education, Tomsk Polytechnic University, Tomsk, Russia, 7-8 September 2000 - Serikova G. N. Galina Nikolaevna (2001, 2001)
В фонде НТБ ТПУ отсутствует